The synergistic antileukemic effects of eltrombopag and decitabine in myeloid leukemia cells - Shi M; Xu F; Yang X; Bai Y; Niu J; Drokow EK; Chen M; Chen Y; Sun K (Cancer Management and Research, 2019)
Mingyue Shi,1–3 Fangfang Xu,4 Xiawan Yang,2 Yanliang Bai,2 Junwei Niu,2 Emmanuel Kwateng Drokow,2 Mingyi Chen,3 Yuqing Chen,2 Kai Sun2 1Division of Graduate, Department of Hematology, The Second Clinical Medical School and the Second Affiliated Hospital of Zhengzhou University, Zhengzhou, People’s Republic of China; 2Department of Hematology, Zhengzhou University People’s Hospital and Henan Provincial People’s Hospital, Zhengzhou, People’s Republic of China; 3Department of Pathology and Laboratory Medicine, UT Southwestern Medical Center, Dallas, TX 75390, USA; 4Department of Research and Discipline Development, Zhengzhou University People’s Hospital and Henan Provincial People’s Hospital, Zhengzhou, People’s Republic of ChinaCorrespondence: Kai Sun; Yuqing ChenDepartment of Hematology, Zhengzhou University People’s Hospital and Henan Provincial People’s Hospital, #7 Weiwu Road, Zhengzhou 450003, Henan, People’s Republic of ChinaTel +86 182 3711 0038Email sunkai@cellscience.org henanblood@sina.comBackground: Hypomethylating agents (HMAs), such as decitabine (DAC), are currently used as first-line therapy for patients with high-risk myelodysplastic syndromes (MDS) and acute myelogenous leukemia (AML) not eligible for standard chemotherapies. Exacerbation of thrombocytopenia is one of the prevalent complications after HMA treatment. Eltrombopag (EP), an oral thrombopoietin receptor agonist, can efficiently stimulate megakaryopoiesis and elevate platelet counts in MDS/AML patients. However, the significance of combining EP with HMAs in patients with high-risk MDS/AML has not been determined.Purpose: To explore the impacts and mechanisms of EP and/or DAC on leukemia cell growth and to explore whether EP exhibits antileukemic effects in the context of DAC treatment in human myeloid leukemia cell lines.Methods: In our study, we assessed the anti-leukemic effect of EP in the context of DAC treatment by measuring cell proliferation, apoptosis, cell-cycle distribution, and intracellular reactive oxygen species (ROS) levels.Results: Our results showed that the combination of EP and DAC had a more obvious antiproliferative effect than that of DAC as a single agent. EP mainly induced S or G0/G1 phase cell cycle arrest, and DAC arrested the cell cycle in the S or G2/M phase. The combination of EP and DAC had a synergistic effect on cell cycle arrest. Furthermore, single-agent treatment with EP or DAC induced a change in intracellular ROS levels, and the combination of EP and DAC had a synergistic effect on ROS levels, exacerbating leukemia cell death.Conclusion: Our study provides in vitro evidence of the synergistic antileukemic effect and potential mechanisms of the combination of DAC and EP on myeloid leukemia cells.Keywords: eltrombopag, decitabine, myeloid leukemia, reactive oxygen species, ROS